Red blood cell aggregate flux in a bifurcating microchannel - Kaliviotis, Efstathios; Pasias, Ioannis; Sherwood, Joseph M.; Balabani, Stavroula (My University, 2017)
Red blood cell aggregation plays a key role in microcirculatory flows, however, little is known about the transport characteristics of red blood cell aggregates in branching geometries. This work reports on the fluxes of red blood cell aggregates of various sizes in a T-shaped microchannel, aiming to clarify the effects of different flow conditions in the outlet branches of the channel. Image analysis techniques, were utilised, and moderately aggregating human red blood cell suspensions were tested in symmetric (similar to 50-50%) and asymmetric flow splits through the two outlet (daughter) branches. The results revealed that the flux decreases with aggregate size in the inlet (parent) and daughter branches, mainly due to the fact that the number of larger structures is significantly smaller than that of smaller structures. However, when the flux in the daughter branches is examined relative to the aggregate size flux in the parent branch an increase with aggregate size is observed for a range of asymmetric flow splits. This increase is attributed to size distribution and local concentration changes in the daughter branches. The results show that the flow of larger aggregates is not suppressed downstream of a bifurcation, and that blood flow is maintained, for physiological levels of red blood cell aggregation.
Keywords: Blood flow; Red blood cell aggregate flux; Micro-PIV; Image processing techniques